Biomedical Engineering 2013
DOI: 10.2316/p.2013.791-038
|View full text |Cite
|
Sign up to set email alerts
|

Low Monomer Content, High Strength Composite Bone Cements

Abstract: The study aim was development of composite bone cements with lower monomer content, viscosity and modulus but a higher conversion and strength than the commercial composite Cortoss TM. Urethane dimethacrylate (UDMA), Triethylene glycoldimethacrylate (TEGDMA) and Hydroxyethyl methacrylate (HEMA) were combined with 0.5 or 1 wt% initiator / activator. This monomer was subsequently combined with 70-80 wt% glass filler. FTIR was used to assess reaction inhibition time and half-life in addition to final monomer conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…This result was confirmed by Khan [16], Liaqat [30], Lygidakis [38], Panpisut et al [39], and Katsimpali [40].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…This result was confirmed by Khan [16], Liaqat [30], Lygidakis [38], Panpisut et al [39], and Katsimpali [40].…”
Section: Discussionsupporting
confidence: 61%
“…Another possible explanation is the presence of calcium/ strontium ions in Breeze, which form complexes with initiators/activators, acting as inhibitors, thereby affecting the curing time and reaction rate [16]. This study showed that adding PLS to either cement has no significant effect on setting time.…”
Section: Data Availabilitymentioning
confidence: 77%
See 1 more Smart Citation